The Efficacy and Difficulties of Implementing a Multifaceted of Strategies to Improve Retainer Compliance: Strategies to Improve Retainer Compliance - Jumani, Sadia Shabbir; Shahid, Rooma; Tanwani, Verkha; Mehmood, Tehreem; Kumari, Payal; Fatima, Kashaf; Mushtaque, Saher (Pakistan Journal of Health Sciences, 2025)
Orthodontic therapy with both permanent and removable appliances is known to be impacted by poor compliance. Objective: To investigate the barriers affecting orthodontic retainer compliance and to explore the effectiveness of a multifaceted approach in enhancing adherence to retainer wear. Methods: In this mixed-methods study, 100 patients were recruited from Jinnah Medical and Dental College, and treatments improved these patients’ retainer compliance. Two groups were made control and intervention in which the control group received orthodontic treatment, and the other group received education, digital tools, and behavioral techniques. For statistical analysis descriptive statistics, logistic regression, and chi-square tests were used, and for qualitative data thematic analysis. Results: The self-reported adherence rates of the control group were higher (78%) as compared to the control group (52%; p < 0.05). The intervention group had higher retention wear adherence than the control group (78% vs. 52%, p < 0.05) which was further confirmed by smart monitoring (6.5 vs. 4.2 nights/week, p = 0.03) and orthodontists (76% vs. 50%, p < 0.05). The impact of digital interventions and behavioral strategies in improving retainer compliance was demonstrated by the compliance-improving techniques that ranked mobile health reminders (82%) as the most effective. Conclusions: A multifaceted approach, such as behavioral approaches, digital technologies, and education, considerably increased retainer compliance. Hence, orthodontic retention regimens that incorporate behavioral techniques and technology may produce improved long-term treatment results.